2021
DOI: 10.3390/md19030120
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of Chito-Oligosaccharides Interactions with Plasma Proteins

Abstract: It is widely recognized that chitin and chitosan are potential sources of bioactive materials and that their oligosaccharides reveal various biological activities (including antimicrobial) that are correlated with their structures and physicochemical properties. This study uses the molecular docking approach to assess the interactions of small chito-oligosaccharides (MW< 1500 Da) with plasma proteins in order to obtain information regarding their fate of distribution in the human organism. There are favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Structures of the protein and terpenes were prepared for docking using the “DockPrep” facility of the Chimera software [ 63 ] that was also used for analysis of the docking outputs. Molecular docking approach has also been used previously in assessing the interactions of numerous types of xenobiotics with human proteins: (i) interactions of chito-oligosaccharides with plasma proteins [ 64 ] and with the myeloid differentiation factor 2 (a protein involved in the inflammatory processes) [ 65 ]; and (ii) interactions of the stereoisomers of the fungicides triticonazole [ 50 ] and difenoconazole [ 66 ] with plasma proteins and cytochromes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Structures of the protein and terpenes were prepared for docking using the “DockPrep” facility of the Chimera software [ 63 ] that was also used for analysis of the docking outputs. Molecular docking approach has also been used previously in assessing the interactions of numerous types of xenobiotics with human proteins: (i) interactions of chito-oligosaccharides with plasma proteins [ 64 ] and with the myeloid differentiation factor 2 (a protein involved in the inflammatory processes) [ 65 ]; and (ii) interactions of the stereoisomers of the fungicides triticonazole [ 50 ] and difenoconazole [ 66 ] with plasma proteins and cytochromes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, COs containing only GlcNAc units revealing higher interaction energies with the two proteins compared with COs containing only GlcN units, and the selectivity of the interactions was dependent on the MW, DaD and AP of COs. 9 It was also true for the interactions between the COs and human plasma proteins (alpha-1 acid glycoprotein and human serum albumin), the interacting energies increased with the molecular weight and with decreasing of deacetylation degree and were dependent on the AP. 7 In addition, a molecular docking study suggested that chitin deacetylases from fungi and marine bacteria were able to bind both totally acetylated and partially acetylated COs, but the binding energy was usually higher in the cases of the interactions with totally acetylated COs. 8 Not at last, COs with different chemical properties revealed quite distinct pharmacological profiles. 6 Results obtained using PLIP software and regarding the types of the interaction between the investigated COs and MD-2 and the amino acids involved in these interactions are presented in TABLE IV.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 A computational study exposed that COs, regardless of their physicochemical properties, revealed promising pharmacological profiles and few toxicological effects on humans: the inhibition of the organic anion transporting peptides OATP1B1 and/or OATP1B3, low potential of cardiotoxicity, and the COs with high DaD exposed the potential of producing phospholipidosis. 6 A molecular docking study revealed favorable interactions of COs with plasma proteins, the interaction energies increasing with the molecular weight (MW), decreasing with increasing DaD and being reliant on the PA. 7 Furthermore, other studies emphasized that the COs characteristics conducted to distinct affinities for chitin deacetylases 8 and lysozyme. 9 The wound healing process depends on four wound healing phases: hemostasis, inflammation, proliferation and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain this information, a computational approach was considered. In the last years, in silico methods have been used to assess the ADMET profiles and to predict the toxicological endpoints of numerous drugs and drug-related chemicals [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ], but also of other xenobiotics, such as phthalates [ 44 ], pesticides [ 12 ], artificial sweeteners [ 45 ], and industrial chemicals [ 46 ]. It emphasizes the applicability of these methods for assessing the biological activity of chemicals.…”
Section: Introductionmentioning
confidence: 99%